Understanding Physics: The Influence of Cognitive Styles and Student Interest - Samsun, Samsun; Tjalla, Awaluddin; Sarifah, Iva (Journal of Comprehensive Science, 2024)
This research investigates the influence of cognitive styles and learning interest on students' understanding of physics concepts. Using a survey method with a sample of 88 first-year students from four programs at a Health Polytechnic in South Jakarta, data were collected through questionnaires on cognitive style perception, learning interest, and a physics concept understanding test. Findings from multiple regression analysis reveal: (1) Cognitive styles and learning interest collectively have a significant influence on physics concept understanding (p = 0.000, F = 26.084); (2) Cognitive style perception independently affects concept understanding (p = 0.047, t = 2.013); and (3) Learning interest significantly impacts concept understanding (p = 0.001, t = 3.426). The study highlights the interplay between cognitive preferences and motivation in achieving mastery of physics concepts.